Conservation Of Archaeological Sites For Eco tourism In Malaysia: Issues & Challenges. - Chia, Dr. Stephen,Ming Soon (Universiti Sains Malaysia, 2003)

(untitled)
Archaeological sites have developed into an essential part of the tourism industry in many countries of the world. In some ~countries, archaeological sites have not only become an important part of the tourism industry but also form a leading sector of the national income, earning millions of dollars every year. These include, amongst others, the terracotta army of China's first emperor in Xian, the ancient pyramids of Egypt and Central America, the stone age cave paintings of Lascaux in France, the ancient temples of Angkor in Cambodia, Borobudur in Indonesia, and Ayutthaya in Thailand.